The Predictive Value of Myeloperoxidase for Contrast-Induced Nephropathy After Percutaneous Coronary Intervention in Patients with Acute Myocardial Infarction - Yan, Gaoliang (Int J Gen Med, 2021)
BACKGROUND: Higher serum myeloperoxidase (MPO) in patients with acute coronary syndrome is associated with adverse cardiovascular outcomes. Contrast-induced nephropathy (CIN) is associated with worse prognosis in patients with coronary artery disease following angiography. We have no idea whether patients with higher serum myeloperoxidase have a higher risk of CIN in acute myocardial infarction (AMI) after percutaneous coronary intervention (PCI). METHODS: This study involved 436 consecutive patients with AMI who had received PCI. Serum MPO levels were determined using enzyme-linked immunosorbent assay before administration of contrast media. Multivariate logistic regression analysis was used to analyze the independent risk factors for CIN after univariate analysis. The receiver operator characteristic (ROC) analysis was performed to evaluate the predictive value of MPO for CIN. RESULTS: Among the 436 patients, 79 individuals (18.1%) suffered CIN after the PCI procedure. Patients who developed CIN had significantly higher MPO levels compared to those who did not ([203.8 (150.6–276.2)] versus [138.5 (129.9–149.2)]; p<0.001). Multivariate logistic regression analysis revealed that MPO level (OR 1.023, 95% CI: 1.017–1.029, p<0.001) was an independent risk factor for the incidence of CIN after adjusting for the baseline information, blood indicators and angiography procedural parameters. The area under the ROC curve for predicting CIN of MPO was 0.848, and the optimum cutoff point of MPO was 147.38ug/L; the sensitivity and specificity were 82.3% and 72.3%, respectively. CONCLUSION: The results show that MPO is independently associated with an increased risk of CIN with AMI patients undergoing PCI. Further studies are needed to verify these results.